Performance over time on adults with simultaneous bilateral cochlear implants. - Chang S; Tyler RS; Dunn CC; Ji H; Witt SA; Gantz B; Hansen M (Journal of the American Academy of Audiology, 2010)
Background: Maximum performance and long-term stability of bilateral cochlear implants has become an important topic because there has been increasing numbers of recipients of bilateral cochlear implants. Purpose: To determine the performance over time (up to 6yr) of subjects with simultaneous bilateral cochlear implants (CI+CI) on word recognition and localization. Research Design: Over-time investigation of word recognition in quiet (CNC) and sound localization in quiet (Everyday Sounds Localization Test). Study Sample: The subjects were 48 adults who simultaneously received their cochlear implants at the University of Iowa. Results: For word recognition, percent correct scores continuously improved up to 1 yr postimplantation with the most benefit occurring within the first month of implantation. In observing up to 72 mo, the averaged scores reached to the plateau of about 63% correct in CNC after 2 yr (N = 31). But, when we followed 17 subjects who have complete data set between 12 mo and 48+ months, word recognition scores were significantly different from 12 mo to 48+ months, which implies binaural advantages need more time to be developed. Localization test results suggested that the root mean square (RMS) error scores continuously improved up to 1 yr postimplantation with most benefits occurring within the first 3 mo. After 2 yr, the averaged scores reached to the plateau of about 20° RMS error (N = 27). When we followed 10 subjects who have complete data set between 12 mo and 48+ months, localization scores were not improved from 12 mo to 48+ months. There were large individual differences in performance over time. Conclusions: In general, substantial benefits in both word recognition and localization were found over the first 1DS12 mo postimplantation for subjects who received simultaneous bilateral cochlear implants. These benefits were maintained over time up to 6yr postimplantation.